Intranasal delivery of human umbilical cord Wharton's jelly mesenchymal stromal cells restores lung alveolarization and vascularization in experimental bronchopulmonary dysplasia. (27th November 2019) - Moreira, Alvaro; Winter, Caitlyn; Joy, Jooby; Winter, Lauryn; Jones, Maxwell; Noronha, Michelle; Porter, Melissa; Quim, Kayla; Corral, Alexis; Alayli, Yasmeen; Seno, Tyrelle; Mustafa, Shamimunisa; et al.
Abstract: Bronchopulmonary dysplasia (BPD) is a devastating lung condition that develops in premature newborns exposed to prolonged mechanical ventilation and supplemental oxygen. Significant morbidity and mortality are associated with this costly disease and effective therapies are limited. Mesenchymal stem/stromal cells (MSCs) are multipotent cells that can repair injured tissue by secreting paracrine factors known to restore the function and integrity of injured lung epithelium and endothelium. Most preclinical studies showing therapeutic efficacy of MSCs for BPD are administered either intratracheally or intravenously. The purpose of this study was to examine the feasibility and effectiveness of human cord tissue-derived MSC administration given via the intranasal route. Human umbilical cord tissue MSCs were isolated, characterized, and given intranasally (500 000 cells per 20 μL) to a hyperoxia-induced rat model of BPD. Lung alveolarization, vascularization, and pulmonary vascular remodeling were restored in animals receiving MSC treatment. Gene and protein analysis suggest the beneficial effects of MSCs were attributed, in part, to a concerted effort targeting angiogenesis, immunomodulation, wound healing, and cell survival. These findings are clinically significant, as neonates who develop BPD have altered alveolar development, decreased pulmonary vascularization and chronic inflammation, all resulting in impaired tissue healing. Our study is the first to report the intranasal delivery of umbilical cord Wharton's jelly MSCs in experimental BPD is feasible, noninvasive, and an effective route that may bear clinical applicability. : Abstract : Intranasal delivery of human umbilical cord mesenchymal stromal cells improves lung growth and development in a rat model mimicking neonatal lung disease.